Biologics for generalized pustular psoriasis: a systematic review and single-arm meta-analysis - Chen, Bai-lin; Liu, Qian-wei; Dong, Xiao-wan; Bai, Yan-ping (Frontiers in Immunology, 2024)
Introduction Generalized pustular psoriasis (GPP) is a rare and potentially life-threatening auto-inflammatory disease. Currently, there are no consensus-based guidelines or universally accepted treatments. Biologics represent a potential therapeutic option. This study systematically assessed the efficacy and safety of biologics in GPP. Methods Relevant studies from three databases were systematically searched until June 28, 2024. Statistical information, including the single-arm proportion rate of the outcomes and 95% confidence intervals (CIs), was analyzed to determine treatment effects. Heterogeneity was assessed using I² values, and subgroup analyses were performed based on drug targets and treatment durations. Data were quantitatively synthesized using a random-effects meta-analysis. Analyses were performed using R statistical software version 4.4.0. Results A total of 329 patients from 16 studies were included. The proportion of responders treated with IL-36 inhibitors and IL-17 inhibitors is higher than those treated with TNF-α inhibitors and IL-23 inhibitors. IL-36 inhibitors appear to achieve the highest response rates between 4 and 8 weeks, while IL-17 inhibitors, TNF-alpha inhibitors, and IL-23 inhibitors show a gradual increase in response rates up to 12 weeks. IL-36 inhibitors achieve a 40% (95% CI: 27%-54%) GPPASI75 response rate and a 55% (95% CI: 41%-68%) GPPGA (0,1) response rate within 2 weeks, significantly outperforming other biologics. The recurrence rates of GPP within 52 weeks, ranked from highest to lowest, are: IL-36 inhibitors (21% [95% CI: 9%-28%]), TNF-alpha inhibitors (20% [95% CI: 2%-46%]), IL-17 inhibitors (15% [95% CI: 1%-37%]), and IL-23 inhibitors (5% [95% CI: 0%-29%]). Additionally, 6% (95% CI: 1%-11%) of patients experienced severe adverse events. Discussion This meta-analysis highlights the efficacy and safety of biologics in patients with GPP, offering valuable evidence to guide future clinical practice. IL-36 inhibitors show a faster and more substantial clinical response in GPP compared to other biologics. Further research is necessary to assess their role in specific subpopulations and to evaluate their potential long-term effects on flare prevention.